Development of dry powder inhaler containing tadalafil-loaded PLGA nanoparticles - Jaleh Varshosaz; Somayeh Taymouri; Hamed Hamishehkar; Razieh Vatankhah; Shadi Yaghubi (Wolters Kluwer Medknow Publications, 2017)
Inhalable dry powders containing poly lactic-co-glycolic acid (PLGA) nanoparticles (NPs) were developed for the delivery of tadalafil (TAD) for treatment of life-treating pulmonary arterial hypertension. Taguchi design was employed to evaluate the effects of different formulation variables on the physicochemical characteristics of PLGA-NPs prepared using emulsion solvent evaporation method. Inhalable PLGA-NPs of TAD were successfully prepared by co-spray drying the PLGA-NPs with inert carriers. Physicochemical characteristics and in vitro deposition of the aerosolized drug were also evaluated. The optimized formulation was prepared using 7.5 mg of PLGA, 2.5 mg of TAD, sonication time of 6 min and 2% polyvinyl alcohol (PVA) as the stabilizer. The optimized aqueous/oil phase ratio for PLGA-NPs preparation was 10:1. Polymer/drug ratio was the most effective parameter on the release efficiency. Encapsulation efficiency, zeta potential and particle size of PLGA-NPs were more affected by aqueous/organic phase ratio. The spray dried powders containing PLGA-NPs had a mass median aerodynamic diameter (MMAD) in the range of 1.4-2.8 μm that was suitable for TAD delivery to the deep region of lung. The presence of L- leucine in mannitol containing formulations decreased the interparticulate forces between particles and increased significantly the process yield and fine particle fraction (FPF). The results indicated that prepared dry powders containing TAD-loaded PLGA-NPs were suitable for inhalation and has the potential for the treatment of pulmonary arterial hypertension.